Incorporating remote sensing techniques to the DRASTIC index to assess groundwater vulnerability at mining areas: application to Sonora river aquifer, northwestern Mexico - Denisse Archundia; Víctor Vidaña-Guillen; Juan Valenzuela-Munguia; Francisco Molina-Freaner (Revista Mexicana de Ciencias Geológicas)
Groundwater metal pollution is a major concern in mining areas. This study proposes a new addition to the DRASTIC method (DRASTIC+Lu) to assess groundwater vulnerability to metal pollution in mining areas by combining remote sensing (to locate metal pollution sources) and the DRASTIC index. The study was performed in a mining area in northwestern Mexico showing current and historical mining activities. The proposed methodology allowed locating known and unknown sources of metal pollution (mining tailings, active/inactive mines, and areas with exposed natural geochemical anomalies). Generally, the addition of the land use (Lu) parameter causes not only a decrease in vulnerability but also highlights very high vulnerable areas and identifies new ones in the vicinity of metal pollution sources. This result is relevant to focus stewardship efforts in very high vulnerable areas. Results allowed to identify the need to implement protection and restauration measures in the Sonora river channel and its vicinity. The proposed method could be implemented in other mining areas around the world –at a low cost– to locate unknown metal pollution sources and clearly identify very high vulnerable areas that play a key role in the protection of groundwater resources.